2015
DOI: 10.1093/jme/tjv117
|View full text |Cite
|
Sign up to set email alerts
|

Streblidae (Diptera: Hippoboscoidea) from Yucatan and Updated Species List for Mexico

Abstract: This study describes the diversity of ectoparasitic bat flies (Diptera: Streblidae) in the state of Yucatan, Mexico. Fieldwork was carried out from June 2010 to January 2012 in seven municipalities of Yucatan, where 13 sampling sites were selected to capture bats using mist nets. Over 156 sampling nights a total of 910 bats were captured; these belonged to 19 species in four families: Mormoopidae, Phyllostomidae, Natalidae, and Vespertilionidae. Phyllostomidae was the richest family (13 bat species), followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 48 publications
3
19
1
5
Order By: Relevance
“…On the other hand, studies in Brazil show a prevalence of 36.88% in São Paulo (Bertola et al, 2005), 29.90% in Pernambuco (Soares et al, 2013), 28.9% in Maranhão (Santos et al, 2009), 23% in Rio de Janeiro (França et al, 2013), and 20.12% in Rio Grande do Sul (Rui & Graciolli, 2005); while Cuxim-Koyoc et al (2015) found a prevalence of 74.06% in Yucatán-México. These differences may be related to the conditions in which the studies were conducted, variations in host and ectoparasites communities, and to different biogeographic history (Rui & Graciolli, 2005;Lourenço et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, studies in Brazil show a prevalence of 36.88% in São Paulo (Bertola et al, 2005), 29.90% in Pernambuco (Soares et al, 2013), 28.9% in Maranhão (Santos et al, 2009), 23% in Rio de Janeiro (França et al, 2013), and 20.12% in Rio Grande do Sul (Rui & Graciolli, 2005); while Cuxim-Koyoc et al (2015) found a prevalence of 74.06% in Yucatán-México. These differences may be related to the conditions in which the studies were conducted, variations in host and ectoparasites communities, and to different biogeographic history (Rui & Graciolli, 2005;Lourenço et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Megistopoda proxima (Séguy, 1926) Material Comentarios: actualmente esta especie representa un complejo de especies que necesita ser aclarado taxonómicamente (Cuxim-Koyoc et al, 2015;Dick, 2013). Los ejemplares recolectados en C. sowelli y T. cirrhosus presentan los caracteres descritos para la especie (tórax comprimido lateralmente, alas ensanchadas con seis venas longitudinales, fémur posterior ligeramente más largo que el abdomen), aunque es necesario recolectar más ejemplares en la región para poder establecer si se trata de una asociación accidental o bien una asociación parásito-hospedero no documentada entre estas especies, pues sus hospederos habituales son especies del género Sturnira (Dick, 2013).…”
Section: Resultsunclassified
“…Comentarios: esta especie, aparentemente característica de murciélagos del género Micronycteris, se ha encontrado en otros hospederos mostrando poca especificidad. En México se le ha registrado únicamente en Yucatán parasitando a T. cirrhosus y M. cozumelae (Cuxim-Koyoc et al, 2015;Guerrero y Morales-Malacara, 1996). El material entomológico aquí estudiado representa un nuevo registro para Veracruz.…”
Section: Strebla Wiedemann 1824unclassified
See 2 more Smart Citations